FOOD AND FEEDING HABITS OF JUVENILES OF 'KOTH' OTOLITHOIDES BRUNNEUS (DAY) IN BOMBAY WATERS - Jayaprakash, A A (Indian Journal of Fisheries, 2011)
The food and feeding habits of juveniles of 'Koth' Otolithoides brunneus(Day), a sciaenid occurring along the coast of Bombay, were studied during theperiod January 1970 — December 1971. O. brunneus a macrophagous carnivore,fed on smaU teleoits and prawns. Index values for main food items during 1970and 1971 were as ibllows: Prawn remains: 46.15, 40.33; Coilia dussumieri: 16.83,28.43; Acetes indicus: 7.32, 15.47; Bregmaceros macclellandi: 18.06, 1.42; Palaemontenuipes: 3.2'[), 5.22; and Hippolysmata ensirostris: 5.29, 0.32 respectively.Besides, teleosts like Otolithes argenteus, Polynemus heptadactylus, Harpodonnehereus, Johnius npp. and Apogon spp., and prawns, such as, Solenocera indica,Metapenaeus affinis M. brevicornis, Parapenaeopsis stylifera and P. hardwickii wereako noticed. The younger juveniles of the size group 7.0 — 13.9 cm preferredonly prawns. Witli age O. brunneus showed a piscivorous tendency. The foodindex value of prawns as a whole decreased from the smallest to the larger sizegroups of 'Koth'. Feeding depended on the availability and no selective feedingwas observed. Intense feeding in April, May and November, normal feedingduring December, January and March and for the rest of the period low feedingseemed to prevail. The probable causes contributing to the intense feeding havebeen discussed